Peningkatan kualitas pembakaran biomassa limbah tongkol jagung sebagai bahan bakar alternatif dengan proses karbonisasi dan pembriketan - Untoro Budi Surono (Jurnal Rekayasa Proses, 2010)
Corn cob is one of potential agricultural wastes in Indonesia that can be processed into an alternative solid fuel. Carbonization (pyrolysis) followed by briquetting is one of the methods that can be applied to process biomass into solid fuels. This work investigated the influence of carbonization temperature and briquetting pressure on combustion characteristic of corn cobs biomass. In this work, carbonization was carried out at three different temperatures, i.e. 220ºC, 300ºC and 380ºC, while briquetting process was prepared using four pressure variations, i.e. 24.4 MPa, 48.8 MPa , 73.2 MPa and 97.6 MPa. The results showed that carbonization process of corn cobs increased the fixed carbon content and the heating value. The best operating condition for carbonization and briquetting process were obtained at temperature of 380ºC and pressure of 97.6 Mpa that could increase the fixed carbon content and the heating value up to 67% and 65% respectively. Carbonization process could reduce CO emission and combustion rate. It was found that a high briquetting pressure resulted in low combustion rate and CO emission.